2017
DOI: 10.5194/acp-17-9399-2017
|View full text |Cite
|
Sign up to set email alerts
|

Plume-exit modeling to determine cloud condensation nuclei activity of aerosols from residential biofuel combustion

Abstract: Abstract. Residential biofuel combustion is an important source of aerosols and gases in the atmosphere. The change in cloud characteristics due to biofuel burning aerosols is uncertain, in part, due to the uncertainty in the added number of cloud condensation nuclei (CCN) from biofuel burning. We provide estimates of the CCN activity of biofuel burning aerosols by explicitly modeling plume dynamics (coagulation, condensation, chemical reactions, and dilution) in a young biofuel burning plume from emission unt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…We speculate that the easily combustible sw pellets with higher burn rate in the FDS resulted in quenching of the flame on the bottom of the pot, leading to enhanced soot emissions, while the pellet mixtures with relatively lower burn rate were likely to result in relatively lower flame height and no quenching of the flame inside the FDS, resulting in low soot emissions. In general, the particle number size distributions compare well with previously published results for comparable experiments (Just et al, 2013;Shen et al, 2017;Mitchell et al, 2019).…”
Section: Particle Number Size Distributionssupporting
confidence: 88%
See 1 more Smart Citation
“…We speculate that the easily combustible sw pellets with higher burn rate in the FDS resulted in quenching of the flame on the bottom of the pot, leading to enhanced soot emissions, while the pellet mixtures with relatively lower burn rate were likely to result in relatively lower flame height and no quenching of the flame inside the FDS, resulting in low soot emissions. In general, the particle number size distributions compare well with previously published results for comparable experiments (Just et al, 2013;Shen et al, 2017;Mitchell et al, 2019).…”
Section: Particle Number Size Distributionssupporting
confidence: 88%
“…The emission factors of CCN for wildfire biomass combustion have been estimated to be on the order of 0.8 × 10 15 to 1.7×10 15 kg −1 relative to the dry mass of various fuels and assuming a supersaturation of 0.5 % (Andreae, 2019). Mena et al (2017) modelled the CCN properties of a residential biomass combustion plume, and they concluded that coagulation limits the CCN emission factor for a supersaturation of 1.0 % to a maximum of 10 16 per kilogram of fuel.…”
mentioning
confidence: 99%
“…The emission factors of CCN for wild fire biomass combustion have been estimated to be at the order of 0.8•10 15 to 1.7•10 15 kg −1 relative to the dry mass of various fuels and assuming a supersaturation of 0.5% (Andreae, 2019). Mena et al (2017) modeled the CCN properties of a residential biomass combustion plume and they concluded that coagulation limits the CCN emission factor for a supersaturation of 1.0% to a maximum of 10 16 per kg of fuel.…”
mentioning
confidence: 99%